AKTIVITAS PEMBELAJARAN DARING DALAM PENINGKATAN MOTIVASI BELAJAR SISWA PADA MASA PANDEMI DI KAMPUNG HEGARMANAH DESA CICANGKANG GIRANG KECAMATAN SINDANGKERTA KABUPATEN BANDUNG BARAT - Saepulloh Saepulloh (Jurnal Al Maesarah, 2022)
Hegarmanah Village, RT. 001 RW. 002 Sindangkerta Village is one of the green zone villages from Covid-19, although the green zone for learning in schools still refers to government regulations to carry out online learning. The purpose of this PKM research is to carry out online learning activities in increasing students' learning motivation. This study used the Mandiri KKN mentoring method, the respondents were 42 students consisting of elementary school students, junior high school students, and high school students. The stages of implementation include observation; activity planning; preparation of activity schedules; implementation of learning; and evaluation stage. The results of Community Service are; students are highly motivated in the learning process; Subject matter assignments from school can be done well; It is hoped that student learning outcomes at school will be better and increase. The response from parents felt happy because it eased the task of parents in guiding their children's learning. Conclusion: online learning activity programs during the pandemic have a positive impact on students' motivation and learning outcomes.